Chlorobenzoic acid degradation by Lentinus (Panus) tigrinus: in vivo and in vitro mechanistic study-evidence for P-450 involvement in the transformation - Stella, T; Covino, S; Křesinová, Z; D'Annibale, A; Petruccioli, M; Čvančarová, M; Cajthaml, T (Journal of hazardous materials, 2013)
Aim of this work was to investigate the ability of Lentinus (Panus) tigrinus to degrade and detoxify a chlorobenzoate (CBA) mixture composed of mono-, di- and tri-chlorinated isomers. The degradation process was investigated as a function of both the growing medium (i.e. low N Kirk's and malt extract-glucose medium) and cultivation conditions (i.e. stationary and shaken cultures). The majority of CBAs were quantitatively degraded within the early 15 d from spiking with the notable exception of the double ortho-chlorinated compounds, 2,6-di-, 2,3,6-tri- and 2,4,6-tri-CBA. Analysis of the degradation intermediates indicated the occurrence of side chain reduction, hydroxylation and methylation reactions. Although CBAs stimulated laccase production, in vitro experiments with a purified L. tigrinus laccase isoenzyme demonstrated its inability to participate in the initial attack on CBAs even in the presence of redox mediators; similar results were found with a Mn-peroxidase isoenzyme. Conversely, prompt degradation was observed upon 1h incubation of CBAs with a purified microsomal fraction containing cytochrome P-450 monooxygenase. The nature of some reaction products (i.e. hydroxylated derivatives), the dependency of the reaction on NADPH and its susceptibility to either CO or piperonyl butoxide inhibition confirmed the involvement of L. tigrinus cytochrome P-450 in the early steps of CBA degradation.
Keywords: biomasa; chemické látky znečišťující vodu; Lentinus tigrinus; Culture Media; Laccase; Biodegradation, Environmental; peroxidasy; Oxygen; čištění vody; Ligninolytic enzymes; Water Purification; kultivační média; Biomass; mikrozomy; Biodegradation; lakasa; Microsomes; luminiscence; Aliivibrio fischeri; Water Pollutants, Chemical; Chlorobenzoates; chlorbenzoáty; Peroxidases; substrátová specifita; systém (enzymů) cytochromů P-450; kyslík; Cytochrome P-450 Enzyme System; Toxicity Tests; Substrate Specificity; testy toxicity; Cytochrome P-450 monooxygenase; Chlorobenzoic acid; chlor; Chlorine; Lentinula; Luminescence; biodegradace